Trophic ecology of fishes associated with artificial reefs assessed using multiple biomarkers - Plumlee, Jeffrey D.; Hala, David N.; Rooker, Jay R.; Shipley, J. Brooke; Wells, R. J. David (Hydrobiologia, 2021)
Understanding trophic relationships within artificial reef communities, especially those of the most numerically abundant fish, provides value to ecologists and managers looking to prioritize healthy food webs. Here we elucidate the trophic interactions of three common fish species on high relief (> 5 m) and low relief (< 5 m) artificial reefs in the northwestern Gulf of Mexico. Biomarkers including stable isotopes, (δ 13 C, δ 15 N, and δ 34 S), and essential fatty acids (18:2n-6, 18:3n-3, 18:4n-3, 20:4n-6, 20:5n-3, 22:5n3, and 22:6n-3) were analyzed within muscle and liver tissue. Species-specific comparisons among tomtate ( Haemulon aurolineatum ), pigfish ( Orthopristis chrysoptera ), and red snapper ( Lutjanus campechanus ), revealed differences in biomarkers within muscle tissue (long-term) namely δ 13 C, δ 15 N, δ 34 S, EPA (20:5n-3), and DHA (22:6n-3). However, using liver tissue (short-term) significant differences existed among a fewer number of biomarkers (δ 15 N, δ 34 S, and EPA) among the three species, indicating increasing trophic similarity. Red snapper collected from low relief reefs had higher δ 15 N values than those on high relief reefs which may be due to higher forage trophic level due to the lack of co-occurring congeners. This study highlights the importance of inter-specific food web observations that aid in the interpretation of the complex trophic relationships occurring on artificial reefs.